Creación de la Iniciativa Nightingale para la Salud Global: reflexiones teóricas para seguir los pasos de Florence Nightingale - Beck, Deva-Marie (2021)
Objective: this paper articulates how three Nightingale scholars applied their theoretical reflections to Florence Nightingale’s farreaching anticipation of the year 1999 and to her comprehensive definition of “Health” derived from her 1893 essay “Sick-nursing and Health-nursing.” Method: this is a historical narrative paper. With intentions to explore how Nightingale’s insights might inform today’s nursing culture and enhance nursing practice, these scholars joined a team of civil society activists to craft the Nightingale Declaration for A Healthy World as the founding credo of the Nightingale Initiative for Global Health. To follow in Nightingale’s footsteps for more than two decades, these scholars since developed methods to increase public awareness of global health concerns and to engage today’s nurses and concerned citizens in this public advocacy. Results: project demonstration results include specific advocacy for the United Nations Millennium Development Goals and Sustainable Development Goals — “Global Goals” targeted to achieve universal outcomes specific to “Health” and across the wider scope of social and environmental health determinants — all anticipated by Nightingale throughout her 40-year career. Conclusion: given today’s severe global health concerns, these scholars’ theoretical reflections identify challenges to contemporary nursing culture — calling for methods developed to strengthen nursing’s voice in the global public arena.